Inhibition of SARS–CoV-2 by type I and type III interferons - Felgenhauer, Ulrike; Schoen, Andreas; Gad, Hans Henrik; Hartmann, Rune; Schaubmar, Andreas R.; Failing, Klaus; Drosten, Christian; Weber, Friedemann (The Journal of biological chemistry, 2020)
The recently emerged severe acute respiratory syndrome coronavirus-2 (SARS–CoV-2) is the causative agent of the devastating COVID-19 lung disease pandemic. Here, we tested the inhibitory activities of the antiviral interferons of type I (IFN-α) and type III (IFN-λ) against SARS–CoV-2 and compared them with those against SARS–CoV-1, which emerged in 2003. Using two mammalian epithelial cell lines (human Calu-3 and simian Vero E6), we found that both IFNs dose-dependently inhibit SARS–CoV-2. In contrast, SARS–CoV-1 was restricted only by IFN-α in these cell lines. SARS–CoV-2 generally exhibited a broader IFN sensitivity than SARS–CoV-1. Moreover, ruxolitinib, an inhibitor of IFN-triggered Janus kinase/signal transducer and activator of transcription signaling, boosted SARS–CoV-2 replication in the IFN-competent Calu-3 cells. We conclude that SARS–CoV-2 is sensitive to exogenously added IFNs. This finding suggests that type I and especially the less adverse effect–prone type III IFN are good candidates for the management of COVID-19.